Incidence of Long-Term Complications in Breast Implant “Prosthesis”: A Systematic Review - Perrotta, Rosario Emanuele; Ronsivalle, Vincenzo; Minervini, Giuseppe; Cicciù, Marco (Prosthesis (Basel, Switzerland), 2025)
Objectives: The term ‘prosthesis’ in reference to breast implants is used to clarify its distinction from the general term ‘breast implant’, which is widely adopted by plastic surgeons. This terminology highlights the role of the implant as a functional tissue substitute, particularly in post-mastectomy reconstruction, rather than solely as a cosmetic enhancement. This distinction is relevant for understanding the long-term implications of implant-based reconstruction and the associated complications. The aim of this systematic review was to compile and analyze the current evidence on the long-term complications associated with breast implants. We explored how these complications vary depending on implant type, surgical techniques, patient-specific factors, and the indication for implantation (cosmetic vs. reconstructive). These indications were analyzed separately to avoid assumptions regarding their correlation with surgical techniques. Methods: A systematic search was conducted across PubMed, Web of Science, and Scopus for studies published up to December 2024, following PRISMA 2020 guidelines and the Cochrane Handbook for Systematic Reviews of Interventions. An initial search identified 1480 studies. After screening and applying inclusion criteria, 11 studies were selected for the final analysis. Studies included in this review reported long-term complications in human subjects, were published in English, and evaluated breast implants. The quality of the included studies was assessed using the ROBINS-E tool. Additionally, subgroup analyses examined differences based on implant type (silicone vs. saline), surgical techniques, and patient characteristics, such as age, comorbidities, and the duration of follow-up. Results: This review study was performed between September 2024 and December 2024. A total of 11 studies were included in the review. The included studies were published between 1997 and 2021, providing a long-term perspective on breast implant complications. The most frequently reported complications were capsular contracture, implant rupture, seroma, and infection, with capsular contracture being the most prevalent. Silicone implants were associated with a higher risk of rupture compared to saline implants. Techniques using textured implants and dual-plane placements were found to reduce the incidence of capsular contracture. Patient-related factors, such as age and smoking status, were identified as significant risk factors for complications, while longer follow-up periods revealed more late-onset complications. Conclusions: This review underscores the importance of understanding the long-term risks of breast implants and highlights the need for personalized surgical planning and thorough follow-up care. Future studies should focus on standardizing outcomes reporting and further evaluating the safety and effectiveness of new implant materials and surgical approaches.